CHRISTIAN PICTURE OF THE WORLD IN GALYNA PAGUTYAK'S NOVEL "URIZHKA GOTHICA": THE ARCHETYPE OF DEATH - Zalevska, Oksana; Bereza, Nataliia (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2025)
Purpose. The article is devoted to the analysis of the novel Urizka Gothic by Halyna Pahutyak through the prism of archetypal criticism. It demonstrates that the vivid archetypal system in the author’s prose – along with her engagement with myth-making, religious motifs, and supernatural plot construction – reflects a distinctive individual style. At the same time, the paper explores significant philosophical and existential motives of the hero's existence. The study also examines in detail the archetype of death, identifying and classifying its various manifestations in Urizka Gothic. Research methodology. In accordance with the topic and issues, the article uses a number of methods that make it possible to highlight the issues raised, in particular - the cultural-historical method (examining the literary work within its cultural and historical context), the psychoanalytic method (analyzing archetypes, artistic imagery, and the semantic layers of the text), the hermeneutic method (interpreting deeper meanings and philosophical dimensions), and the structural-functional method (exploring the modified structure of scholarly interpretation and the interrelations among its elements). Results. The article comprehensively argues and proves the thesis about the peculiarities of Halyna Pahutyak's mythological thinking based on the material of the novel Urizka Gothic. It elucidates the concept of the ‘archetype’ and applies it to trace distinctive phenomena within the content-rich narrative of this contemporary Ukrainian writer. The results of the study make it possible to find out the functionality of the archetype of death in the novel, as well as to determine the place and role of the author of Urizka Gothic in the current national literary process. The practical significance. The findings of this study can be used in further research on Halyna Pahutyak’s text, particularly in the context of archetypal criticism within modern Ukrainian literature.